Pharmacokinetics and Safety of Ranirestat in Patients With Hepatic Impairment. (21st May 2020) - Itou, Minoru; Fujita, Tomoe; Inoue, Kazuaki; Uchida, Naoki; Takagaki, Takeshi; Ishii, Daisuke; Kakuyama, Hiroyoshi
Abstract: Ranirestat is an aldose reductase inhibitor hypothesized to improve diabetic neuropathy. An open‐label, single‐dose, parallel‐group study was conducted to compare pharmacokinetic (PK) characteristics of an oral dose of ranirestat across subjects with normal hepatic function and patients with mild and moderate hepatic impairment because ranirestat is expected to be used by patients with diabetes mellitus, possibly including those with hepatic impairment. To evaluate the necessity for dose adjustment, PK profiles and tolerability were studied at the dose of 40 mg, the expected optimal clinical dose in patients with diabetic neuropathy and normal hepatic function. In total, 20 subjects, including 5, 10, and 5 subjects with normal hepatic function, mild hepatic impairment, and moderate hepatic impairment, respectively, completed the study. Serial PK sampling was conducted up to 504 hours, and PK parameters were calculated and compared between healthy subjects and patients with mild or moderate hepatic impairment. The geometric mean ratios of peak concentration and area under the concentration‐time curve in patients with mild hepatic impairment (90%CI) were 86.7% (55.3% to 135.9%) and 84.7% (68.5% to 104.8%), respectively. The values in patients with moderate hepatic impairment were 81.3% (48.8% to 135.5%) and 91.7% (72.1% to 116.7%), respectively. These results demonstrated that plasma ranirestat exposure and the plasma protein binding of the drug were not substantially altered by normal, mild, or moderate hepatic impairment (protein binding 99.22%, 99.29%, and 99.00%, respectively). All adverse events were mild in severity. Based on these findings, no dose adjustment will be required for ranirestat in patients with mild or moderate hepatic impairment.